2021
DOI: 10.3390/foods10123144
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Analysis to Understand the Expected Benefits by Plant-Based Meat Alternatives Consumers

Abstract: The plant-based alternative meat products market has attracted attention in recent years, as the demand for these products has grown worldwide. To meet the needs of this promising market, marketers must pay attention to the expected benefits of consumers and the insights that can be gleaned from comments posted on social media. This article proposed an investigation of the potential of the content analysis of comments posted on the Instagram social network of food companies that manufacture plant-based alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…PBMA food marketing teams must extol the advantages of PBMA in various ways and promote it actively by providing information about its positive effects in engaging ways, such as by involving popular figures. Moreira et al [ 67 ] indicated that social media use is effective in maintaining a positive relationship between PBMA manufacturers and consumers. Willett et al [ 3 ] stressed that the government should strongly regulate advertising and marketing for unhealthy and unsustainable foods and provide consumer education on healthy diets that promote the consumers’ health and sustainability of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…PBMA food marketing teams must extol the advantages of PBMA in various ways and promote it actively by providing information about its positive effects in engaging ways, such as by involving popular figures. Moreira et al [ 67 ] indicated that social media use is effective in maintaining a positive relationship between PBMA manufacturers and consumers. Willett et al [ 3 ] stressed that the government should strongly regulate advertising and marketing for unhealthy and unsustainable foods and provide consumer education on healthy diets that promote the consumers’ health and sustainability of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The recent body of literature on plant-based milk alternatives covers various consumer behaviours such as willingness to buy, willingness to pay a price premium, and consumer segments [1,2,[13][14][15], with studies dedicated to consumer attitudes and preferences [16][17][18][19]. Understanding how consumers perceive food and beverages is important for creating new products, diversifying product assortments, meeting the needs of different consumer groups, and generating their loyalty [19][20][21]. In this light, insights into consumers' willingness to try plant-based milk alternatives are as essential as understanding their word-of-mouth sharing.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have provided essential evidence on the factors of plant-based meat’ consumption, there is a lack of exploration in specific contexts, mainly in social media marketing ( Qutteinq et al, 2019 ; He et al, 2020 ). Social media marketing is more in line with the habits of young people, significantly improving the interaction between consumers and plant-based meat ( Moreira et al, 2021 ). Specifically, consumers rely on expert opinions, friend recommendations, and advertising on social media to acquire knowledge of plant-based meat and be influenced by them ( Thompson et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%